When Childcare is Commodified: An Autoethnography of Urban Mothering in Yogyakarta, Indonesia - Solekhah, Nuzul (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
The research explores how motherhood constructs parenting spaces in urban contexts and, conversely, how urban spaces construct urban motherhood. This autoethnographic research uses Edward Soja’s concept of third space. The results of this study show that working mothers’ routines position them in terms of categorizing time, namely time for work and time for parenting, with a preference for parenting space outside the home. This practice simultaneously constructs temporal (time of care) and spatial (space of care) understandings for children and parents. Social media accelerates the spread of information about leisure centers, including the segmentation of care spaces. The creation of these new care spaces shows that the commodification of urban mothering is slowly shifting the role of care from the home to the public sphere. On the other hand, this domestication of the caring space can involve men in caring practices and change the stigma that caring is not only a woman’s role. Despite thearticulation of parenting as a lifestyle, the infrastructure of parenting spaces and playgrounds for children is still far from meeting the criteria of public space, as the majority are commodified, especially in the context of this research, Yogyakarta.